Suppose a function f is such that f ( x 1 ) − 3 f ( x ) = x for every x = 0 . Find f ( 2 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Create a system of equations with two variables. In this case, 2 and 2 1 would be smart to use for x as there will only be two variables, f ( 2 ) and f ( 2 1 ) . 1 . f ( 2 1 ) − 3 f ( 2 ) = 2 2 . f ( 2 ) − 3 f ( 2 1 ) = 2 1 Now, substitute and solve. Isolating f ( 2 ) in equation 2: f ( 2 ) = 2 1 + 3 f ( 2 1 ) Substituting into equation 1: f ( 2 1 ) − 3 ( 2 1 + 3 f ( 2 1 ) ) = 2 f ( 2 1 ) − 2 3 − 9 f ( 2 1 ) = 2 − 8 f ( 2 1 ) = 2 7 f ( 2 1 ) = − 1 6 7 Plugging back into equation 1: − 1 6 7 − 3 f ( 2 ) = 2 − 3 f ( 2 ) = 1 6 3 9 f ( 2 ) = − 1 6 1 3 f ( 2 ) = − 0 . 8 1 2 5
Bad solution
plug in 1/x and then solve f(x) you get: -(3x/8+1/8x) plug in 2 and you'r done
Problem Loading...
Note Loading...
Set Loading...
Alternatively, the solution steps can be done using a symbolic algebra system, in this case sympy. You still must know how to solve the problem.